Penerapan Metode Mastery Learning pada Animated Pedagogical Agent (APA) untuk Pembelajaran Aksara Jawa - Aryasatya Okta Pradhana; Ati Suci Dian Martha; Anisa Herdiani (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Javanese script learning is learned by students in elementary schools in Tuban, East Java. However, students still do not understand this Javanese script learning material. This is related to students' low interest in learning. This research aims to evaluate the impact of the application of mastery learning method through Animated Pedagogical Agent on students' interest level in learning Javanese characters. In addition, to develop a learning application "Aksara" as a tool for learning Javanese script at the elementary school level. To assess the impact of the Animated Pedagogical Agent in the application in increasing students' interest in learning, this study used a Non Randomized Control Group Pretest-Posttest Design with an additional questionnaire of learning interest as an indicator of learning interest assessment in testing the application of mastery learning methods. The experimental results show that the learning application "Aksara" with Animated Pedagogical Agent has a good effect on increasing students' interest in learning and mastery learning in the application also provides an understanding of the Javanese script sandhangan material. This research contributes to teachers to increase the effectiveness of learning Javanese characters at the elementary school level through applications with the support of Animated Pedagogical Agent.